Indexing of Indian Journals in SCImago Citation Database: A Decadal Study (2005-2014) - Singh, Shivendra; Pandita, Ramesh (DESIDOC Journal of Library & Information Technology, 2016)
The present study seeks to examine the growth of Indian research journals indexed by SCImago Journal and Country Ranking, based on SCOPUS data sources. The study covers the period 2005-2014. Some of the key aspects projected in the study includes, the distribution of Indian research journals indexed by SCOPUS during the last decade, annual corresponding growth of journals indexed, subject wise distribution of Indian journals indexed, India’s share percentage of journals indexed by SCOPUS both at the continental and the global level. The study also examines the distribution of journals and their growth at the subject level. From the analysis, it emerged that India is the 6th largest country to have maximum (452) journals indexed by the SCImago citation index. Of the total journals indexed by SCOPUS 1.97% are from India. The overall indexing of Indian journals during the decade has recorded a growth of 131.79%, but the number is very abysmal, when compared to the number of journals indexed from other smaller European countries. At the continental level (Asia), 16.95% journals indexed are from India.